Frequency-reuse planning of the down-link of distributed antenna systems with maximum-ratio-combining (MRC) receivers - Castañeda-Trujillo, E. (2011)
Distributed antenna systems (DAS) have been shown to considerably outperform conventional cellular systems in terms of capacity improvement and interference resilience. However, the influence of frequency reuse planning on the performance of DAS remains relatively unknown. To partially fill this gap, this paper presents a comparative analysis of the down-link of DAS versus conventional cellular systems using different values of frequency reuse factor. The analysis assumes Rayleigh fading channels and it also considers maximum-ratio-combining (MRC) receivers at the user terminals to exploit diversity both in the transmission and reception links. Numerical evaluation of the analytical expressions shows that, in general, for most of the cases DAS can achieve better performance figures than conventional cellular systems using considerably smaller values of frequency reuse factor. Conversely, DAS can significantly improve the throughput (2x-3x) and power consumption (6-10 dB) of conventional systems when using the same frequency reuse factor. An interesting result shows that in some particular cases DAS outperform conventional cellular systems no matter the frequency reuse factor used by the latter one, which indicates an effective capacity gain provided by the combined operation of DAS and MRC receivers.